Equipment to avaliate erosion caused by water-solid mix on hydraulic surfaces - Gallani, Guilherme Rasera; Filho, Jose Gilberto Dalfre; Branco, Renan de Lima; Malavasi, Stefano (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
The surfaces of hydraulic structures may suffer erosion damages caused usually by abrasion or cavitation. Abrasive erosion is caused by the friction and the impact of water-solid mix and in cavitation erosion, bubbles implosions can lead to huge erosion, and many other related problems. In order to guarantee the safety of the structures, both effects must be analyzed. Different concretes may present several performances when exposed to abrasion and cavitation erosion. Therefore, this research evaluated the effect of differents coarse aggregates on concrete resistence to erosion by abrasion and by cavitation.